Automobile electrical and electronic systems - Denton, Tom (Automotive technology: vehicle maintenance and repair series, 2017)
"As electrical and electronic systems become increasingly more complex and fundamental to the workings of modern vehicles, understanding these systems is essential for automotive technicians. For students new to the subject, this book will help to develop this knowledge, but will also assist experienced technicians in keeping up with recent technological advances. This new edition includes information on developments in pass-through technology, multiplexing, and engine control systems."--Back cover